Pre-professional practice systematization and its relationship to research skills - Guerra Ayala, Margit Julia (2023)
This article focuses on the examination of pre-professional practice systematization and proposes a theoretical-methodological model that draws from Oscar Jara’s framework and incorporates insights from neuroscience and critical complex thinking. The objective is to enhance the understanding and implementation of effective pre-professional practice. A sample of 1,150 students was selected from four universities and a pedagogical institute in Peru to investigate the systematization processes, efficiency levels, and research skill articulation of pre-professional practice. Among them, 289 students were chosen to participate in the application of the proposed model. Data collection was conducted using a virtual survey and questionnaire, employing descriptive-correlative and quasi-experimental designs. The study revealed a concerning level of inadequacy and limited research capacity in pre-professional practice systematization. The analysis also established a significant relationship between these variables and demonstrated the positive impact of the model’s application within an experimental group. Based on these findings, it is recommended that institutions allocate more resources and create additional opportunities for comprehensive systematization during pre-professional practice. This will facilitate the development of research skills among students and adequately prepare them for future research engagement. Overall, this study underscores the importance of an efficient systematization approach in pre-professional practice, highlighting the need for institutions to prioritize research skill cultivation in their educational programs.